REVISION Y FILOGENIA DE LAS POLILLAS DEL GENERO LEUCOLITHODES WARREN, 1904 (GEOMETRIDAE: ENNOMINAE) - Parra, Luis E.; Hormazabal, Monica E. (Acta Entomológica Chilena, 2022)
The systematic status of the genus Leucolithodes Warren, 1904 is reviewed. Bryoptera Guenée, 1857 is not present in Chile, the species formerly assigned to it are in fact Leucolithodes paulina, (Ureta, 1956) n. comb., L. panteata (Felder & Rogenhofer, 1875) and L. lecideata (Felder & Rogenhofer, 1875). Description of the imago, phylogeny, distributions and flight period of these species are given. Genitalia of the male and female are illustrated and photographs of the adults are presented.